Perubahan Pola Ruang Pasca Pandemi dalam Sektor Wisata Khususnya pada Rumah Produktif Perajin Perak Kampung Basen - Steffany Hartono; Wiyatiningsih (ATRIUM: Jurnal Arsitektur, 2022)
Title: Changes in Post-Pandemic Spatial Patterns in The Tourism Sector, Case Study: The Productive House of Silver Artisans in Basen Village   The Covid-19 pandemic in recent years has brought many changes to various sectors of life. In the tourism sector, the decline in tourist numbers makes the tourist spots change to maintain existence. This research aims to find changes in the spatial elements and the pattern of productive houses after the pandemic and evaluate resident adaptation to the spatial changes. This research uses a qualitative descriptive method, by raising a study case of three silvers-productive houses affected by the Covid-19 pandemic. Data retrieval is made through observation of changes in resident activity patterns and changes in the interior function of productive houses. Research results in analyzing new elements, space patterns, and residents' adaptation. Changes in spatial patterns experienced by productive houses of silver artisans occurred due to changes in residents' livelihoods due to the Covid-19 pandemic. Changes in semi-fixed elements are found in all case studies, as it is the easiest to manage the needs of its residents. This study will provide insight into the spatial pattern of the silver artist's house in Basen Village and evaluate the resident's adaptation to changes in spatial pattern.